Preparação e caracterização de nanocompósitos a base de poli(álcool vinílico) carregados com nanopartículas de propriedades bactericidas via eletrofiação - Costa, Rodrigo Guerreiro Fontoura (2011)
The work in this thesis mainly focuses on the preparation and characterization of poly(vinyl alcohol) (PVOH)-based nanocomposites loaded with nanoparticles of titanium dioxide (TiO2 anatase and TiO2 prepared by hydrothermal treatment) and silver (Ag) designed to test the bactericidal activity of such materials. For this purpose, PVOH aqueous solutions at concentrations of 10 wt.% and 18 wt.% were electrospun. Results of the morphological characterization showed that the average diameters of these fibers are in the range of 77 to 155 nm. Subsequently, the poly(vinyl alcohol)(PVOH)/silver (Ag) nanocomposites were prepared by electrospinning process. These nanofibers were characterized by SEM, EDS, XRD, UV-Vis diffuse reflectance spectroscopy and MET. SEM images have shown the average diameter of electrospun fibers of around 90 nm. TEM images have shown the nanoparticles homogeneously dispersed in the fiber, with an average diameter of 5,8 nm. These materials demonstrated significant antibacterial activities against Stapylococcus aureus (87,8%) and Escherichia coli (85,0%). Likewise, this work presents the characterization of PVOH/TiO2 (anatase, commercial) and PVOH/TiO2 (hydrothermal) nanocomposites. These nanofibers were characterized by SEM, XRD, EDS, TEM, UV-VIS diffuse reflectance spectroscopy, TG, and DSC. The TiO2 loading have been shown to be effective in the nanocomposite, changing the UV absorbance. In an attempt to offer an indirect assessment of the antibacterial activities of these nanocomposites, photocatalytics experiments were carried out using a dye, Rhodamine B (RhB), that have been used to probe the activity of TiO2. Although the degradation degree of RhB using nanofibers of PVOH/TiO2 (anatase) and PVOH/TiO2 (hydrothermal) is lower than nanopowders of TiO2 (anatase) and TiO2 (hydrothermal), conversely, the results have shown that nanofibers have photoactivity indicating that some nanoparticles of TiO2 were on the surface, degrading RhB. However, the PVOH photocatalytic degradation experiment showed that only the TiO2 nanoparticles (anatase and spherical in shape) degraded the PVOH. The results showed that the total weight loss percentage of PVOH in the PVOH/TiO2 fiber is 56% after 1 hour irradiation. The PVOH in nanocomposite PVOH/TiO2 (5wt.%) (hydrothermal) was not degraded due to the rodshaped nanoparticles of TiO2 and the predominance of the rutile crystalline phase, which is known to have less and poor photocatalyst activity than TiO2 anatase phase. In this study, PVOH/TiO2 (anatase), PVOH/TiO2 (hydrothermal), and PVOH/Ag nanocomposites are considered to be promising materials for application in the food industry.